Herd Structure, Performance Traits, Pattern of Calving and Culling in an Organized Large Herd of Gir Cattle - Gadariy, MR; Vataliya, PH; Murthy, KS; Savsani, HH (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Herd structure and herd performance traits of Gir herd of Cattle Breeding Farm, JAU, Junagadh, Gujarat was studied utilizing monthly data over a period of 10 years (2001-2010). A herd with an average of 110 Gir cows had average total strength of 388.38±3.09 and total adult units (AUs) of 259.27 ±13.42. The total females present in the herd were 71.82%. The Gir herd consisted of 28.98 % cows, 22.02 % breedable heifers, 22.34 % calves (female + male) and 12.33 % males above 1 year. Wet average and herd average were 6.77±0.10 and 3.84±0.06 lit/d/cow, and % milch cows and number of milch cows were 57.03±0.85 and 63.12±1.42, respectively. Effect of month was significant on the herd average only. All herd performance traits were significantly influenced by year. Return over feed cost (ROFC) at variable feed cost was estimated to be 116.36±4.24 % at market rate of milk. Calving incidence was significantly (P6 lactation) and low yield. Maximum cows, 26.21% were disposed of in their 3rd lactation. Growing/breeding males were sold @ 28.57% and castrated males to the tune of 22.32 %. The correlations among the herd structure and performance traits of the herd were negative, medium in magnitude and significant, - 0.21 to - 0.29 with wet average, -0.16 to -0.21 with herd average and -0.25 to -0.73 (P7.32 lit/d/milch cow) and herd average (> 4.17 lit/d/cow) and also higher ROFC >139.6 %.
Keywords: Gir cattle; Herd structure; Herd performance; Calving pattern; Culling